Detection of stiction in flow control loops based on fuzzy clustering. (June 2015) - Daneshwar, M.A.; Mohd Noh, Norlaili
Abstract: In the presence of stiction, the control valves may present an oscillatory behaviour that affects the regulatory control performance, thereby causing a loss of product quality and increasing energy consumption. Detection of stiction in the early phase is a crucial key for process control to avoid major disruptions to the plant operations. In this paper, a novel technique based on a well-developed fuzzy clustering approach is proposed. Based on a dramatic change of the slope of the lines obtained from successive cluster centres in the presence of stiction, a new performance index to distinguish the cause of oscillation is proposed. The simulation, experimental and industrial results are provided. Highlights: Flow control loops form significant control loops in industry. The applications of shape-based techniques of stiction detection are limited. The proposed technique does not rely on the shape of the stiction pattern.